Are We Ready for Nosocomial Candida auris Infections? Rapid Identification and Antifungal Resistance Detection Using MALDI-TOF Mass Spectrometry May Be the Answer - De Carolis, Elena; Marchionni, Federica; La Rosa, Marilisa; Meis, Jacques F.; Chowdhary, Anuradha; Posteraro, Brunella; Sanguinetti, Maurizio (Frontiers in Cellular and Infection Microbiology, 2021)
The occurrence of multidrug-resistant Candida auris isolates and the increased mortality associated with invasive infections or outbreaks due to this Candida species have been reported in many healthcare settings. Therefore, accurate and rapid identification at the species level of clinical C. auris isolates as well as their timely differentiation as susceptible or resistant to antifungal drugs is mandatory. Aims of the present study were to implement the MALDI-TOF mass spectrometry (MS) Bruker Daltonics Biotyper® database with C. auris spectrum profiles and to develop a fast and reproducible MS assay for detecting anidulafungin (AFG) resistance in C. auris isolates. After creation of main C. auris spectra, a score-oriented dendrogram was generated from hierarchical cluster analysis, including spectra of isolates from C. auris and other Candida (C. glabrata, C. guilliermondii, C. haemulonii, C. lusitaniae, and C. parapsilosis) or non-Candida (Rhodotorula glutinis) species. Cluster analysis allowed to group and classify the isolates according to their species designation. Then, a three-hour incubation antifungal susceptibility testing (AFST) assay was developed. Spectra obtained at null, intermediate, or maximum AFG concentrations were used to create composite correlation index matrices for eighteen C. auris isolates included in the study. All six resistant C. auris isolates were detected as resistant whereas 11 of 12 susceptible C. auris isolates were detected as susceptible by the MS-AFST assay. In conclusion, our MS-based assay offers the possibility of rapidly diagnosing and appropriately treating patients with C. auris infection.